2018
DOI: 10.3386/w24315
|View full text |Cite
|
Sign up to set email alerts
|

Do Human Capital Decisions Respond to the Returns to Education? Evidence from DACA

Abstract: This paper studies human capital responses to the availability of the Deferred Action for Childhood Arrivals (DACA) program, which provides temporary work authorization and deferral from deportation for undocumented, high-school-educated youth. We use a sample of young adults that migrated to the U.S. as children to implement a difference-indifferences design that compares non-citizen immigrants ("eligible") to citizen immigrants ("ineligible") over time. We find that DACA significantly increased high school a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The first finding, that health improved in the short term, is consistent with past research on the immediate post-DACA period, which found that DACA increased high school graduation rates, labor-force participation, and wages and decreased poverty. 14,15,17,36 Existing studies also link DACA to improvements in the mental health of DACA-eligible immigrants 19,20 and their children 18 in the short-term post-policy period. A variety of mechanisms related to socioeconomic status and socioemotional transformations may explain improvements to health in the shortterm period following DACA's announcement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first finding, that health improved in the short term, is consistent with past research on the immediate post-DACA period, which found that DACA increased high school graduation rates, labor-force participation, and wages and decreased poverty. 14,15,17,36 Existing studies also link DACA to improvements in the mental health of DACA-eligible immigrants 19,20 and their children 18 in the short-term post-policy period. A variety of mechanisms related to socioeconomic status and socioemotional transformations may explain improvements to health in the shortterm period following DACA's announcement.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] By granting eligible undocumented immigrants protection from deportation and some fundamental rights, DACA may have improved the health of participants and their children. [14][15][16][17][18][19][20][21] However, DACA recipients do not have access to permanent legal status or a guarantee that their temporary status will remain in place. Indeed, the program's future has been highly uncertain since 2015, leading one journalist to describe the experience as a "political and legal limbo[,] …a kind of purgatory [for DACA recipients]."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first year of DACA, the take‐up rate was around 30% (Kuka, Na'ama, and Shih ). Recent data from the Migration Policy Institute (MPI) show that, as of August 2018, 700,000 people in the United States were DACA recipients.…”
mentioning
confidence: 99%
“…For studies of the programs' effects on participants' economic outcomes, see, for example, Amuedo-Dorantes and Antman (2016) andKuka, Shenhav, and Shih (2018) on DACA and Orrenius and Zavodny (2015b) on TPS.…”
mentioning
confidence: 99%